Eve dan Lilith dalam Konsep Wanita Judaisme - Mohd Khambali @ Hambali, Khadijah; Basiron, Bushrah (Jurnal Usuluddin, 2009)
The article attempts to discuss on issues related to Eve and Lilith as the important women according to Judaism. It discusses Eve as the first woman created by God according to the Torah and Lilith as an extremely controversial figure within Jewish folklore and Midrash. These two figures; Eve and Lilith are the keyword to understand the concept of women according to Judaism.